Macroeconomic and agricultural reforms in Zimbabwe: policy complementaries toward equitable growth - Bautista, Romeo M.; Thomas, Marcelle (International Food Policy Research Institute, 2000)
Using a CGE (computable general equilibrium) model for Zimbabwe with 1991 as base period, this paper examines quantitatively the income and equity effects of macroeconomic reform measures in isolation and in conjunction with potentially complementary changes in agricultural sector policies. Some important features of the CGE model are an explicit focus on agriculture, distinction among various rural and urban household groups, and detailed specification of factor markets. Specific aspects of economic policy existing in the pre-reform benchmark year are taken into account in the base model, such as the administered setting of the foreign exchange rate, quantitative import restrictions, and government-determined maize prices for domestic producers and grain millers. The model makes use of a 1991 SAM (social accounting matrix) for Zimbabwe as database.